MAKNA PRAGMATIK BAHASA VERBAL DAN NONVERBAL KINESTETIK SEBAGAI MANIFESTASI KESANTUNAN MASYARAKAT SUNDA: KAJIAN ETNOPTAGMATIK - Neneng Tia Ati Yanti; Pranowo Pranowo; R. Kunjana Rahardi (Kajian Linguistik dan Sastra, 2020)
This research describes the pragmatic meaning of verbal and nonverbal language of Sundanese people in Sindangkasih District, Ciamis Regency, West Java. This research is a qualitative research using ethnopragmatics. That is, verbal and nonverbal politeness of Sundanese people can be done through speech acts that use kinesthetic nonverbal language (facial, gestural, and postural). The data source of this research is routine activities carried out by Sundanese people in Sindangkasih Subdistrict. The data in this study are verbal and nonverbal languages that contain politeness. The technique of collecting data in this study was to adapt the ethnographic method and use the method of listening. The data analysis technique of this study uses a flow model consisting of data reduction, data presentation, drawing conclusions and verification. The results showed that the pragmatic meaning of verbal and nonverbal politeness of Sundanese people was manifested through kinesthetic nonverbal language, namely nonverbal facial language (facial expressions / facial expressions); gestural (eye movements, head movements, and hand movements); and postural (movements of all limbs, such as bowing, standing upright, leftward, and rightward).Keywords: Verbal language, nonverbal language, and politeness